2015
DOI: 10.4103/2230-8210.167565
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus species: An emerging pathogen in onychomycosis among diabetics

Abstract: Introduction:Approximately, 33% patients with diabetes are afflicted with onychomycosis. In the past, nondermatophyte molds have been regarded as opportunistic pathogens; recently, Aspergillus species are considered as emerging pathogens of toenail infections. In Sri Lanka, the prevalence of Aspergillus species in onychomycosis among diabetics is not well documented.Objective:To determine the proportion of Aspergillus onychomycosis, risk factors and knowledge among diabetics.Materials and Methods:This was desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Some investigations reported that A. fumigatus is more common in the Western countries, whereas A. flavus is more prevalent in the Asia and Middle East. 31 , 32 In the present work, 33.3% of cases with onychomycosis were recognized; while, Veer et al, 33 and Wijesuriya et al, 34 reported 48.885% of onychomycosis from India and Sri Lanka, respectively. Naghibzadeh et al, 35 detected 1.2% of Aspergillus sinusitis in Tehran, Iran, from 2007 to 2009, whereas 15.9% of Aspergillus sinusitis was reported in the present research.…”
Section: Discussionsupporting
confidence: 43%
“…Some investigations reported that A. fumigatus is more common in the Western countries, whereas A. flavus is more prevalent in the Asia and Middle East. 31 , 32 In the present work, 33.3% of cases with onychomycosis were recognized; while, Veer et al, 33 and Wijesuriya et al, 34 reported 48.885% of onychomycosis from India and Sri Lanka, respectively. Naghibzadeh et al, 35 detected 1.2% of Aspergillus sinusitis in Tehran, Iran, from 2007 to 2009, whereas 15.9% of Aspergillus sinusitis was reported in the present research.…”
Section: Discussionsupporting
confidence: 43%
“…The latter is an emerging onychomycosis pathogen among diabetics, and the risk of having Aspergillus nail disorders among patients being treated for diabetes increases with the duration of the disease [ 64 ]. In a study conducted in India among patients who were involved in agricultural activities, 77% were diabetic and were confirmed to have Aspergillus onychomycosis [ 64 ]. Nail damage can be noticed in HIV patients and in patients with hormonal imbalance induced by Cushing’s syndrome and hypothyroidism.…”
Section: Risk Factorsmentioning
confidence: 99%
“…7 Fungal species, mainly yeasts and Aspergillus species, are commonly associated with patients with diabetes mellitus. 8 C. albicans accounts for > 90% of oral and systemic candida infections followed by C. tropicalis, C. parapsilosis, C. glabrata and C. krusei. 9,10 Ayurvedic rasayana consisting of Amulaki/Nelli (Emblica officinalis), Bibhitaki/Bulu(Terminalia bellirica) and Halituki/Aralu (Terminalia chebula) commonly known as "Triphala" is effectively used in Ayurveda.…”
Section: Introductionmentioning
confidence: 99%